2012
DOI: 10.1021/cg201447c
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Porous Metal–Organic Frameworks of Co(II) and Ni(II): Synthesis, Structure, Magnetic Properties, and CO2 Uptake

Abstract: Four isostructural chiral three-dimensional (3D) porous pillared-layer frameworks based on Co(II) and Ni(II), {[M(l-mal)(azpy)0.5]·2H2O} n (M = Co (1), Ni (2)) and {[M(l-mal)(bpee)0.5]·H2O} n (M = Co (3), Ni (4)); (l-mal = l-malate dianion, azpy = 4,4′-bisazobipyridine, and bpee = 1,2-bis(4-pyridyl)ethylene), have been synthesized using mixed ligand systems and characterized structurally. All the frameworks are homochiral, based on the chiral l-malate dianion. The bridging of l-malate with Co(II) or Ni(II) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 54 publications
(56 reference statements)
4
70
0
Order By: Relevance
“…As the aromatic rings present in the azoCOPs cannot be the reason for N 2 phobicity 19,20 , we studied the effects of the -N ¼ N-moieties in the framework on the near rejection of N 2 at higher temperatures, 323 K, as well as the temperature dependence of the increased selectivity. Incidentally, similar observations have been noted in a very recent report 49 , where azo-bridged linkers are compared with ethylenic ones in crystalline metal-organic frameworks (MOFs) for CO 2 uptake. The authors, however, ignored the obvious N 2 -phobic behaviour of azo-MOFs when N 2 uptakes are compared.…”
Section: Synthesissupporting
confidence: 82%
“…As the aromatic rings present in the azoCOPs cannot be the reason for N 2 phobicity 19,20 , we studied the effects of the -N ¼ N-moieties in the framework on the near rejection of N 2 at higher temperatures, 323 K, as well as the temperature dependence of the increased selectivity. Incidentally, similar observations have been noted in a very recent report 49 , where azo-bridged linkers are compared with ethylenic ones in crystalline metal-organic frameworks (MOFs) for CO 2 uptake. The authors, however, ignored the obvious N 2 -phobic behaviour of azo-MOFs when N 2 uptakes are compared.…”
Section: Synthesissupporting
confidence: 82%
“…In addition to the findings of photoresponsive function, research has suggested that MOFs incorporating azobenzene ligands display an increased affinity for CO 2 , [44] and that azobenzene exhibits a degree of N 2 phobicity that enhances its selectivity for CO 2 over N 2 . [45] Herein, we detail the synthesis and characterisation of a new coordination framework incorporating the novel azo-containing ligand 5-((4-tert-butyl)phenylazo)isophthalic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Versatile carboxylate ligands derived from 1,4-benzenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid, or pyridine-2,4-dicarboxylic acid are commonly used owing to their abundant carboxylate groups possessing high affinity to metal cations [7][8][9]. Other functionalized ligands such as 1,2-bis(4-pyridyl)ethylene, 1,4-benzenediacetic acid, 4,4 -bipyridylethene, or 3-nitro-1,2-benzenedicarboxlic acid have also been extensively used under diverse synthetic conditions to prepare MOFs [10][11][12][13][14][15][16][17], which are used in several applications [18][19][20][21][22]. The interest in the use of phenylenediacetic acid as ligand in the synthesis of coordination polymers stems from the presence of the flexible −CH 2 spacer that enables the −CO 2 − units to freely bend and rotate to meet the requirements of the coordination geometries of metal ions in the assembly process [23].…”
Section: Introductionmentioning
confidence: 99%